Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s11356-023-26239-3
|View full text |Cite
|
Sign up to set email alerts
|

Coupling ANFIS with ant colony optimization (ACO) algorithm for 1-, 2-, and 3-days ahead forecasting of daily streamflow, a case study in Poland

Abstract: Finding an efficient and reliable streamflow forecasting model has always been an important challenge for managers and planners of freshwater resources. The current study, based on an adaptive neuro-fuzzy inference system (ANFIS) model, was designed to predict the Warta river (Poland) streamflow for 1 day, 2 days, and 3 days ahead for a data set from the period of 1993–2013. The ANFIS was additionally combined with the ant colony optimization (ACO) algorithm and employed as a meta-heuristic ANFIS-ACO model, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Furthermore, Alquraish et al ( 2021 ) demonstrated the versatility of combining ANFIS with meta-heuristics across multiple domains by using ANFIS with meta-heuristic algorithms to forecast reservoir inflow forecasting for the King Fahd Dam, Saudi Arabia, which supports the notion that improving predicting results can be achieved by combining ANFIS with meta-heuristic optimization techniques. The hybridization of ANFIS with meta-heuristic optimization algorithms such as genetic algorithm (GA) (Alquraish et al 2021 ) and ant colony optimization (ACO) (Aghelpour et al 2023 ) has been studied in the context of PET forecasting. As per Mehdizadeh et al ( 2021 ), shuffled frog-leaping algorithm (SFLA) and invasive weed optimization (IWO) have demonstrated their ability to estimate daily reference evapotranspiration accurately.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Alquraish et al ( 2021 ) demonstrated the versatility of combining ANFIS with meta-heuristics across multiple domains by using ANFIS with meta-heuristic algorithms to forecast reservoir inflow forecasting for the King Fahd Dam, Saudi Arabia, which supports the notion that improving predicting results can be achieved by combining ANFIS with meta-heuristic optimization techniques. The hybridization of ANFIS with meta-heuristic optimization algorithms such as genetic algorithm (GA) (Alquraish et al 2021 ) and ant colony optimization (ACO) (Aghelpour et al 2023 ) has been studied in the context of PET forecasting. As per Mehdizadeh et al ( 2021 ), shuffled frog-leaping algorithm (SFLA) and invasive weed optimization (IWO) have demonstrated their ability to estimate daily reference evapotranspiration accurately.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao [42] proposed a value prediction and analysis method of network documents based on ant colony algorithm. Aghelpour et al [43] coupled adaptive neuro-fuzzy inference system with ant colony optimization algorithm to realize the 1-, 2-, and 3-days ahead forecasting of daily streamflow. Albashish and Aburomman [44] proposed a heterogeneous ensemble classifier configuration based on ant colony optimization for a multiclass intrusion detection problem.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the results of these methods to those of classical ANFIS and found that these methods were more successful than classical ANFIS for modeling and predicting air pollution. To find an efficient and reliable streamflow forecasting model, Aghelpour et al [25] developed an ANFIS model coupled with an ant colony optimization (ACO) algorithm to predict the streamflow of a river for 1 day, 2 days, and 3 days ahead. They found that the accuracy of the simple ANFIS model obtained was good.…”
Section: Introductionmentioning
confidence: 99%